2005
DOI: 10.1021/jo050956y
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrolled Synthesis of a Complex Library via Elaboration of Angular Epoxyquinol Scaffolds

Abstract: We have accomplished the synthesis of a complex chemical library via elaboration of angular epoxyquinol scaffolds with distinct skeletal frameworks. The key strategy involves highly stereocontrolled [4 + 2] Diels-Alder cycloadditions of chiral, nonracemic epoxyquinol dienes to generate the scaffolds. Further scaffold diversification involves hydrogenation, epimerization, dehydration, and condensation of the carbonyl group with alkoxyamine and carbazate building blocks. Further elaboration of the scaffolds also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Synthetic targets include, the heterocyclic core of GE 2270 [34], peridinin [35], pyrones isolated from placobranchus ocellatus [36], terpenepolyketide natural products [37], dihydroxerulic and xerulinic acid [38], bipinnatin J [39], elipticine [40], (+)-7-deoxytrans-dihydronarciclasine [41], gambierol [42], taiwaniaquinol [43], (−)-scabronine G [44], garsubellin A [45], piericidin A1 and B1 [46], lucilactaene [47], fostriecin [48], lupine alkaloids [49], ␤-C-glycosides [50], (+)-crocacin D [51], lobatamide analogs [52], epoxyquinoid compounds [53,54], (+)-SCH 351448 [55], 3-methyl-2,5-dihydro-1-benzoxepin carboxylic acids [56], (+)-ochromycinone and (+)-rubiginone B 2 [57], EI-1941-1 and EI-1941-2 [58], mycothiazole [59], 6 -epiperidinin [60], aureothin and N-acylaureothamine [61], cyercene A and placidenes [62], herbindole B [63], (+)-tubelactomicin A [64], saudin [65], peroxyacarnoates A and D [66], aureothin, N-acetylaureothamine, aureonitrile [67], elysiapyrones [68], altromycin B [69], (+)-phorboxazole A and analogues [70,71], (−)-SNF4435 C and (+)-SNF4435 D [72], A2E [73], paracentrone [74]<...>…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…Synthetic targets include, the heterocyclic core of GE 2270 [34], peridinin [35], pyrones isolated from placobranchus ocellatus [36], terpenepolyketide natural products [37], dihydroxerulic and xerulinic acid [38], bipinnatin J [39], elipticine [40], (+)-7-deoxytrans-dihydronarciclasine [41], gambierol [42], taiwaniaquinol [43], (−)-scabronine G [44], garsubellin A [45], piericidin A1 and B1 [46], lucilactaene [47], fostriecin [48], lupine alkaloids [49], ␤-C-glycosides [50], (+)-crocacin D [51], lobatamide analogs [52], epoxyquinoid compounds [53,54], (+)-SCH 351448 [55], 3-methyl-2,5-dihydro-1-benzoxepin carboxylic acids [56], (+)-ochromycinone and (+)-rubiginone B 2 [57], EI-1941-1 and EI-1941-2 [58], mycothiazole [59], 6 -epiperidinin [60], aureothin and N-acylaureothamine [61], cyercene A and placidenes [62], herbindole B [63], (+)-tubelactomicin A [64], saudin [65], peroxyacarnoates A and D [66], aureothin, N-acetylaureothamine, aureonitrile [67], elysiapyrones [68], altromycin B [69], (+)-phorboxazole A and analogues [70,71], (−)-SNF4435 C and (+)-SNF4435 D [72], A2E [73], paracentrone [74]<...>…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…This library contains arrays of chemically diverse molecules derived from synthetic methods developed at the CMLD-BU. [11][12][13][14] The compounds were solubilized in 100% DMSO and the library was formatted at the HTS facility at The Scripps Research Institute-Scripps Florida. The compounds were screened at 15 μM fi nal concentration.…”
Section: Cmld-bu Librarymentioning
confidence: 99%
“…Finally, 1 and 71.2). These two products upon heating with a primary amine in the presence With the goal of obtaining angular epoxyquinol scaffolds, which are commonly found in a wide variety of bioactive natural products, Porco and co-workers 433 Shaw and co-workers 434 demonstrated that a linear synthetic sequence, differing only by the incorporation of a single functional group, could produce different core 3D architectures. The solid-phase variant of an enantioselective Suga-Ibata reaction 435 was adopted to synthesize 73.3 (Scheme 73) in high yields and with complete diastereoselectivity.…”
Section: Solid-phase Synthesis Of Alkaloid Natural Product-inspired Cmentioning
confidence: 99%